Overexpression of ornithine decarboxylase 1 mediates the immune-deserted microenvironment and poor prognosis in diffuse large B-cell lymphoma - Xiaojie Liang; Jia Guo; Xiaofang Wang; Baiwei Luo; Ruiying Fu; Haiying Chen; Yunong Yang; Zhihao Jin; Chaoran Lin; Aimin Zang; Youchao Jia; Lin Feng; et al. (Journal of the National Cancer Center)
Background: Previous researches mainly focused on whether cancer stem cells exist in diffuse large B-cell lymphoma (DLBCL). However, subgroups with dismal prognosis and stem cell-like characteristics have been overlooked. Methods: Using large scale data (n = 2133), we conducted machine learning algorithms to identify a high risk DLBCL subgroup with stem cell-like features, and then investigated the potential mechanisms in shaping this subgroup using transcriptome, genome and single-cell RNA-seq data, and in vitro experiments. Results: We identified a high-risk subgroup (25.6 % of DLBCL) with stem cell-like characteristics and dismal prognosis. This high-risk group (HRG) was featured by upregulation of key enzyme (ODC1) in polyamine metabolism and cold tumor microenvironment (TME), and had a poor prognosis with lower 3-year overall survival (OS) (54.3 % vs. 83.6 %, P < 0.0001) and progression-free survival (PFS) (42.8 % vs. 74.7 %, P < 0.0001) rates compared to the low-risk group. HRG also exhibited malignant proliferative phenotypes similar to Burkitt lymphoma. Patients with MYC rearrangement, double-hit, double-expressors, or complete remission might have either favorable or poor prognosis, which could be further distinguished by our risk stratification model. Genomic analysis revealed widespread copy number losses in the chemokine and interferon coding regions 8p23.1 and 9p21.3 in HRG. We identified ODC1 as a therapeutic vulnerability for HRG-DLBCL. Single-cell analysis and in vitro experiments demonstrated that ODC1 overexpression enhanced DLBCL cell proliferation and drove macrophage polarization towards the M2 phenotype. Conversely, ODC1 inhibition reduced DLBCL cell proliferation, induced cell cycle arrest and apoptosis, and promoted macrophage polarization towards the M1 phenotype. Finally, we developed a comprehensive database of DLBCL for clinical application. Conclusions: Our study effectively advances the precise risk stratification of DLBCL and reveals that ODC1 and immune-deserted microenvironment jointly shape a group of DLBCL patients with stem cell-like features. Targeting ODC1 regulates immunotherapies in DLBCL, offering new insights for DLBCL treatment.